2011
DOI: 10.1590/s1516-35982011001200039
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of lambs fed diets with fat and vitamin E

Abstract: -This experiment aimed to determine the influence of diets with inclusion of protected fat and vitamin E on performance, yield and carcass characteristics of feedlot lambs with different weights. Thirty-two non-castrated Santa Ines lambs were fed diets with a ratio of 40% forage and 60% concentrate ad libitum, with presence or absence of protected fat and/or vitamin E, in a total of four diets. Two weights of early containment were also considered: between 20 and 25 kg and between 30 and 35 kg. All animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Vitamin E supplementation also did not alter the performance variables. These findings corroborate the observations of Pinto et al, (2011), who investigated Santa Ines sheep supplemented with 500 mg/head/day of vitamin E and found no differences in performance variables by the addition of the vitamin. Supplementation can influence performance characteristics when diet levels do not reach the minimum level required for the body to Lightness (L*); intensity of yellow (a*); intensity of green (b*); shear force (SF); weight loss from cooking (WLC); C= castrated; S= supplemented with vitamin E; NS= not supplemented.…”
Section: Castration and Vitamin E In Lambssupporting
confidence: 92%
“…Vitamin E supplementation also did not alter the performance variables. These findings corroborate the observations of Pinto et al, (2011), who investigated Santa Ines sheep supplemented with 500 mg/head/day of vitamin E and found no differences in performance variables by the addition of the vitamin. Supplementation can influence performance characteristics when diet levels do not reach the minimum level required for the body to Lightness (L*); intensity of yellow (a*); intensity of green (b*); shear force (SF); weight loss from cooking (WLC); C= castrated; S= supplemented with vitamin E; NS= not supplemented.…”
Section: Castration and Vitamin E In Lambssupporting
confidence: 92%
“…Chapman and Ward (1979) concluded that the pentose phosphate pathway is active in follicles to supply the high level of pentose required for the synthesis of nucleic acid for cell division and protein synthesis in the follicle. The changes in the carbohydrate content in the present study may be due to the presence of pearl millet, which is considered as a source of energy as well as the supplementation of the feed mixture with protected fat, that reduces the dry matter intake and increases the ether extract consumption (Pinto et al, 2011).…”
Section: Fig (1)mentioning
confidence: 84%
“…On another point of view, the use of protected fat in the diet influenced significantly consumption of all nutrients (Pinto et al, 2011). They also stated that the use of protected fat in the diet of Santa Ines lambs reduces the dry matter intake and increases the ether extract consumption.…”
Section: Fig (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…On another point of view, the use of protected fat in the diet influenced significantly consumption of all nutrients (Pinto et al, 2011). The non-influence of the protected fat on fibre growth is probably due to the fact that part of the fat source is inactive in the rumen and probably what was fermented in this compartment was not enough to negatively influence the food degradation so it could affect animal performance.…”
Section: Table (1)mentioning
confidence: 99%